2014
DOI: 10.7897/2321-6328.02123
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Therapeutic Application of Fasd (Venesection) in Unani Medicine

Abstract: According to Unani medicine, Health is attributed to the equilibrium of akhlat (humours) in the body, according to their quality and quantity, while disease occurs due to disturbances in this equilibrium. Fasd is one of the methods of evacuation of morbid matter from the body for the preservation and restoration of health. Venesection is carried out when there is excess of blood in the body and patient is either at risk of developing a disease or has actually developed it. In present era it is known as phlebot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…22 Venesection ( fasd ) on median cubital vein (behind the ear) 23 and also wet cupping are applied for vertigo and dizziness in Unani medicine. 24 It seems that the effect of bloodletting on the blood flow and blood supply of the brain is one of the causes of its effect on vertigo and dizziness. 25 …”
Section: Discussionmentioning
confidence: 99%
“…22 Venesection ( fasd ) on median cubital vein (behind the ear) 23 and also wet cupping are applied for vertigo and dizziness in Unani medicine. 24 It seems that the effect of bloodletting on the blood flow and blood supply of the brain is one of the causes of its effect on vertigo and dizziness. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Sū'-i-mizāj is further classified into two types viz. (i) sū'-i-mizāj sāda (dystemperament not associated with morbid humours), (ii) sū'-i-mizaj māddī (abnormal substantial temperament) [4]. When three basic causes are present together, the disease condition is called marz-i-murakkab (compound/composite disease).…”
Section: Unani Medicinementioning
confidence: 99%
“…In modern era, this regimenal therapy has been discarded because some studies have suggested that after phlebotomy certain pathological conditions are developed but thousand year observation of Unani physicians, it cannot be discarded merely on the basis of modern studies which have been carried out on small sample size. Hence, more studies may be carried out on large sample size to validate scientifically this old age regimen [4]. (3).…”
Section: Mode Of Unani Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…preventing accumulation of waste material in the blood, excreting waste material from various parts of the body, stimulating metabolic processes and correcting altered temperaments. Contraindications reported by Khan, Siddiqui, Itrat and Jamal (2014) include applying procedure in excessively cold temperament and climate, in cases of severe pain, after coitus, in children less than fourteen years of age, obesity, in elderly persons, with a full stomach, after resolving baths, and during pregnancy or menstruation.…”
Section: Venesectionmentioning
confidence: 99%